2022
DOI: 10.1371/journal.pone.0273800
|View full text |Cite
|
Sign up to set email alerts
|

Variation in detected adverse events using trigger tools: A systematic review and meta-analysis

Abstract: Background Adverse event (AE) detection is a major patient safety priority. However, despite extensive research on AEs, reported incidence rates vary widely. Objective This study aimed: (1) to synthesize available evidence on AE incidence in acute care inpatient settings using Trigger Tool methodology; and (2) to explore whether study characteristics and study quality explain variations in reported AE incidence. Design Systematic review and meta-analysis. Methods To identify relevant studies, we queried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 97 publications
0
6
1
2
Order By: Relevance
“…This is also considerably lower than our corresponding estimate for GTT/TT studies at 24.8 and 103.6 (general care and intensive care populations) AEs per 100 admissions. On the other hand, a newly published systematic review29 including GTT/TT studies in general care reported a pooled incidence of 30.0 AEs per 100 adult admissions which is higher compared with our findings in the general care population.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…This is also considerably lower than our corresponding estimate for GTT/TT studies at 24.8 and 103.6 (general care and intensive care populations) AEs per 100 admissions. On the other hand, a newly published systematic review29 including GTT/TT studies in general care reported a pooled incidence of 30.0 AEs per 100 adult admissions which is higher compared with our findings in the general care population.…”
Section: Discussioncontrasting
confidence: 84%
“…In a recently published meta-analysis for adult inpatients, some of the variation could be explained by those methodological aspects (type of hospital included, age of sample included and experience of the review team). 29 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation for the variation of AE rates may be the patients' care need, as patients in need of complex medical procedures are more likely to experience AEs 18 . Another reason may be related to methodological differences, for example, the AE definition used and time frame of AE detection 19 . The high rate of AEs in the present study might partly be explained by the 88 triggers including ‘other’ as an alternative.…”
Section: Discussionmentioning
confidence: 80%